The men who wipe out billions - Monblat, Jeremy; BBC worldwide (North Sydney, N.S.W. : BBC Worldwide, 2002)
It has wiped out around £3 billion in the savings of ordinary investors whilst the money men behind it have earned millions in commissions and bonuses. The Money Programme investigates the massive and growing scandal of split capital trusts. Reporter Michael Robinson goes on the trail of the men behind this financial disaster to find out why, among other pressing questions, did the'zero' investments they loudly proclaimed as safe turn out so calamitously risky?
Title from title screen
Camera, Jon Stapleton, Tony Poole ; sound, Eric Fever, Simon Parmenter
DVD format
Keywords: Portfolio management -- Great Britain; Pension trusts -- Great Britain; Mutual funds -- Great Britain; Finance, Personal -- Great Britain; Capital investments -- Great Britain